2010
DOI: 10.1111/j.1476-5381.2010.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A, a naturally occurring inhibitor of fatty acid amide hydrolase

Abstract: Background and purpose: Inhibitors of fatty acid amide hydrolase (FAAH), the enzyme responsible for the metabolism of the endogenous cannabinoid (CB) receptor ligand anandamide (AEA), are effective in a number of animal models of pain. Here, we investigated a series of isoflavones with respect to their abilities to inhibit FAAH. Experimental approach: In vitro assays of FAAH activity and affinity for CB receptors were used to characterize key compounds. In vivo assays used were biochemical responses to formali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 61 publications
2
32
0
1
Order By: Relevance
“…Previous in-vivo study reported that biochanin-A is a naturally occurring inhibitor of FAAH, which metabolites endocannabinoids [20]. However, the efficacy of biochanin-A is higher at 2 h post-dose in both hyperalgesia and allodynia.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous in-vivo study reported that biochanin-A is a naturally occurring inhibitor of FAAH, which metabolites endocannabinoids [20]. However, the efficacy of biochanin-A is higher at 2 h post-dose in both hyperalgesia and allodynia.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, biochanin-A behaved like URB597 after local administration to the paw [20]. Thus, biochanin-A could be suitable drug candidate for neuropathic pain patients in alleviating majorly mechanical allodynia and moderately mechanical hyperalgesia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, since the interaction is mixed-type instead of competitive, the relative K i will never be higher than 1 μM. Isoflavones, including Biochanin A, have been reported to inhibit FAAH in a similar mixed-type fashion (Thors et al, 2010). Several of these isoflavones have similar structural features including a para phenol to the carbonyl group.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both AEA (via CB 1 cannabinoid receptors) and 2-AG (via CB 2 cannabinoid receptors) are efficacious in the formalin test when given locally to the hind paws of rats (Guindon et al, 2006(Guindon et al, , 2007, and that FAAH inhibitors reduce the behavioral and biochemical consequences of formalin in this test (Lichtman et al, 2004;Sit et al, 2007;Clapper et al, 2010;Thors et al, 2010), inhibition of FAAH could in theory be involved in the action of HD. The compound, however, was a rather weak inhibitor of FAAH in vitro, producing inhibition of AEA hydrolysis only at concentrations of 20 μM and higher.…”
Section: Role Of Faah Inhibition In the Antinociceptive Effects Of Hdmentioning
confidence: 98%